Analisis Keragaman Fitoplankton di Sungai Barumun Kecamatan Panai Tengah Kabupaten Labuhanbatu - Sari Mawaddah Harahap; Arman Harahap (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Research on the analysis of the diversity of phytoplankton has been carried out in the Barumun River, Panai Tengah District, Labuhanbatu Regency. The Barumun River is widely used by the surrounding community for various activities, for example: disposal of industrial waste, household waste, fish auctions, ports, and fishing. This activity resulted in the Barumun River being polluted with increasingly turbid water color. The purpose of this study was to determine the diversity of phytoplankton in the Barumun River. This type of research is a descriptive research with a quantitative approach. Sampling used Plankton Net mesh size 30 μm from 3 stations with 10 repetition, observed using a microscope, identified using the book "Marine and Fresh Plankton", counted, and analyzed the diversity index of plankton in the Zoology Laboratory, Biology Education Department, FKIP, University Labuhanbatu. Plankton abundance was calculated using the Lackey Drop micro-count method and Plankton diversity was calculated using the Shannon-Wiener formula. The results showed that the phytoplankton found were dominated by Diatoms and Dinoflagellates, with the highest average abundance being from the genus Cerratulina (1015 ind/L), and the lowest abundance value was from the Protoperidiun genus (5 ind/L). The diversity index is included in the moderate diversity category (1.48-1.90), and the dominance index is in the range of 0.24-0.28 with a low category.